How School can Teach Civic Engagement Besides Civic Education: The Role of Democratic School Climate. Issue 3 (30th August 2014) - Lenzi, Michela; Vieno, Alessio; Sharkey, Jill; Mayworm, Ashley; Scacchi, Luca; Pastore, Massimiliano; Santinello, Massimo
Abstract: Civic engagement, defined as involvement in community life, is influenced by reciprocal relationships between individuals and contexts and is a key factor that contributes to positive youth development. The present study evaluates a theoretical model linking perceived democratic school climate with adolescent civic engagement (operationalized as civic responsibility and intentions for future participation), taking into account the mediating role of civic discussions and perceived fairness at school. Participants were 403 adolescents (47.9 % male) ranging in age from 11 to 15 years old (mean age = 13.6). Path analysis results partially validated the proposed theoretical model. Higher levels of democratic school climate were associated with higher levels of adolescent civic responsibility; the association was fully mediated by civic discussions and perceived fairness at school. Adolescents' civic responsibility, then, was positively associated with a stronger intention to participate in the civic domain in the future.